Revision of total knee arthroplasty with press-fit condylar SIGMA TC3-mobile bearing system and porous metaphyseal sleeves in type AORI type II and III bone defects. A long-term follow-up study: Porous metaphyseal sleeves in knee defects - Zanchini, Fabio; Piscopo, Davide; Pola, Enrico; Cipolloni, Valerio; Piscopo, Antonio; Cacciapuoti, Stefano; Colò, Gabriele; Fusini, Federico (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Revision total knee arthroplasty(rTKA) is a challenging and expensive treatment for orthopedic surgeons who have to deal with poor bone quality and bone loss. This study aims to retrospectively evaluate the clinical and radiological results of patients undergoing rTKA and porous metaphyseal sleeves in AORI type II and III bone defects.Methods: We conducted a retrospective series of continuous patients treated for mechanical failure of TKA. All patients with aseptic loosening of TKR underwent revision arthroplasty. We included only patients with AORI type IIa/b and III bone defects. The Septic revision or other grades of bone defect or patients lost at follow-up or with less than 2 years follow-up were excluded. We evaluated knee function with Oxford Knee Score (OKS) pain with Visual Analogue Scale (VAS) and range of motion (flex-ext), while radiological evaluation was performed to evaluate any sign of loosening.Results: The mean preoperative OKS was 13.85 +/- 5.39 (range 5 -22), and it improved to 33.89 +/- 3.98 (range 20 - 40) (p